Assessment for community participation in solid waste management in urban settlements: A case study of Mbeya city council - Said, Yahaya H. (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirement for award of the degree of Master of Research and Public Policy (MRPP) of the Mzumbe University